Struktur Pembangun dalam Kumpulan Puisi Jejak-jejak Pena - Jumadi Jumadi; Sitti Hasriyati Anies; Herniyastuti Herniyastuti; Muhammad Yunus (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstract: The Building Structure in a Collection of Pen Trail Poems. This study aims to examine the building structure contained in the collection of poems Traces of the Pen. The purpose of this study is to describe the physical structure and inner structure in the poetry collection Traces of the Pen. This type of research is descriptive using a qualitative approach. The source of this research data is the collection of poems Traces of Pen Traces. The resulting data is in the form of sentences, phrases, and words. Data collection techniques use read and record techniques. The data processing technique used is collection. selection, and organization. The data analysis technique used is content analysis. The research validity checking techniques used are triangulation, intensive guidance, and peer discussion. Based on the results of the study, it can be concluded as a whole that in the collection of poems Traces of the Pen has a physical structure and an inner structure. Physical structure includes diction, imagining, concrete words, majas, verification. and typography. Then, the inner structure includes feelings, and commissions. theme, tone, word.